2013
DOI: 10.15835/nsb549178
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Several Popular Cultivars of Madagascar Periwinkle (<i>Catharanthus roseus</i> (L.) G. Don.) using Biochemical Markers

Abstract: Band designs of esterase (EST), peroxidase (PO) and polyphenol oxidase (PPO) isozymes in several selected cultivars of Catharanthus roseus by using native polyacrylamide gel electrophoresis (PAGE) were investigated in this study. It was confirmed that cultivar differences in isozyme polymorphism can be revealed by applied electrophoretic patterns. Three isozyme systems produced a total of 16 bands with polymorphism ranged from 66.6-100%. Considering the patterns of isozyme variations in the five cultivars of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…As a genetic marker, isozymes can be considered highly important in polymorphic studies. The polymorphic validity of isozyme data in studies of plant biodiversity has been shown by Kumar et al (2013). Moreover, a good point was made by Khan et al (2010), who stated that isozymes are a useful marker for genetic polymorphism within the plant group structure.…”
Section: Discussionmentioning
confidence: 99%
“…As a genetic marker, isozymes can be considered highly important in polymorphic studies. The polymorphic validity of isozyme data in studies of plant biodiversity has been shown by Kumar et al (2013). Moreover, a good point was made by Khan et al (2010), who stated that isozymes are a useful marker for genetic polymorphism within the plant group structure.…”
Section: Discussionmentioning
confidence: 99%